Immobilization of Horseradish Peroxidase onto Montmorillonite/Glucosamine–Chitosan Composite for Electrochemical Biosensing of Polyphenols - Piccoli, María Belén (2024)
Glucosamine–chitosan synthesized by the Maillard reaction was combined with montmorillonite to obtain a nanohybrid composite to immobilize horseradish peroxidase. The material combines the advantageous properties of clay with those of the chitosan derivative; has improved water solubility and reduced molecular weight and viscosity; involves an eco-friendly synthesis; and exhibits ion exchange capacity, good adhesiveness, and a large specific surface area for enzyme adsorption. The physicochemical characteristics of the composite were analyzed by infrared spectroscopy and X-ray diffraction to determine clay–polycation interactions. The electrochemical response of the different polyphenols to glassy carbon electrodes modified with the composite was evaluated by cyclic voltammetry. The sensitivity and detection limit values obtained with the biosensor toward hydroquinone, chlorogenic acid, catechol, and resorcinol are (1.6 ± 0.2) × 102 µA mM−1 and (74 ± 8) nM; (1.2 ± 0.1) × 102 µA mM−1 and (26 ± 3) nM; (16 ± 2) µA mM−1 and (0.74 ± 0.09) μM; and (3.7± 0.3) µA mM−1 and (3.3 ± 0.2) μM, respectively. The biosensor was applied to quantify polyphenols in pennyroyal and lemon verbena extracts.